2000
DOI: 10.1163/156854100509439
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity of populations of the entomopathogenic nematodes Steinernema feltiae and Heterorhabditis megidis in relation to temperature, age and lipid content

Abstract: The infectivity of populations of the entomopathogenic nematodes Steinernema feltiae and Heterorhabditis megidis from Greece (GR) and the UK was compared using Galleria mellonella larvae as hosts. Dose-response tests showed that the two Steinernema populations did not differ in their establishment rates but they were more infective than H. megidis UK 211. The temperature range for infectivity was greater than that for development. However, the optimal temperature for infection and development for all populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…This is probably not the case. Wright et al (1997), Grewal (2000), and Menti et al (2000) showed that S. feltiae IJs do not age rapidly. If whole life spans were considered, S. carpocapsae and H. bacteriophora might age in a more linear fashion, decreasing in infectiousness at a constant rate with time, whereas S. feltiae ages bimodally (Hay and Fenlon, 1995) or at different rates with time (Bohan and Hominick, 1997).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is probably not the case. Wright et al (1997), Grewal (2000), and Menti et al (2000) showed that S. feltiae IJs do not age rapidly. If whole life spans were considered, S. carpocapsae and H. bacteriophora might age in a more linear fashion, decreasing in infectiousness at a constant rate with time, whereas S. feltiae ages bimodally (Hay and Fenlon, 1995) or at different rates with time (Bohan and Hominick, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…In this experiment, old nematodes were not extremely old in comparison with the typical IJ life span. Although older than Ͻ1-wk-old IJs, 2-to 4-wk-old S. feltiae IJs are rather young, considering they can live for several months (Grewal, 2000;Menti et al, 2000). It is, therefore, understandable that old and young S. feltiae were infectious.…”
Section: Discussionmentioning
confidence: 99%
“…Attraction decreasing for 140 days and 180 days of storage time might be due to further declining energy (lipid) reserves as suggested by nematode bodies becoming increasingly transparent. The consumption of these reserves is thought to be associated with a decline in the ability to infect (Griffin, 2012;Menti et al, 2000). This phenomenon could be explained by phased infectivity in which infectivity is changed associated with aging (Dempsey and Griffin, 2002;Griffin, 2012;Ryder and Griffin, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…But Menti et al (2000) mentioned that this is not always the case because when they compared two S. feltiae and two Heterorhabditis megidis isolates recovered from Greece and UK, they didn't Wnd obvious diVerence between the isolates. In addition, the cold-adapted S. feltiae has been isolated from tropical Hawaii, and it still retains its coldadapted traits (Hazir et al, 2001).…”
Section: Discussionmentioning
confidence: 99%